Teacher Perceptions of the Usefulness of ‘MI-ROBOT’ for Enhancing Linguistic and Kinesthetic Skills in Children with Special Needs - Taryudi, Taryudi; Djatmiko, Wisnu; Kusuma, Murti; Lindayani, Linlin (Journal of Educational Science and Technology (EST), 2025)
This study aimed to evaluate the perceived usefulness of a teaching robot, Mi-Robot, in delivering linguistic and kinesthetic stimulation for children with special needs, based on teacher feedback. The study employed a mixed-methods design and involved 20 special education teachers from five inclusive schools in Bandung, West Java, Indonesia. Teachers participated in a 32-hour training program focused on integrating Mi-Robot into classroom activities. Data were collected using the Mi-Robot Acceptance Scale and an open-ended evaluation form. Quantitative data were analyzed using descriptive statistics, while qualitative responses were examined through thematic content analysis. Teachers reported high acceptance levels, with mean scores above 4.0 across all four TAM dimensions. Qualitative findings revealing that Mi-Robot was seen as curriculum-compatible, engaging, and cost-effective. Features such as gamification, visual appeal, and customizable challenges were noted to enhance student motivation and facilitate individualized learning. Participants expressed a strong intention to integrate Mi-Robot into their future teaching practices. Mi-Robot is perceived as a promising educational tool for supporting the development of linguistic and kinesthetic intelligence in children with special needs. Its usability, adaptability, and alignment with inclusive education goals make it suitable for classroom and distance learning contexts.